Optimization of Idle Assets of the Ketapang Regency Government with the Highest And Best Use Method to Increase Local Original Income - Rosyadi, Rosyadi; Prislyawan, Prima Febria; Sulistiawati, Rini (Ridwan Institute, 2023)
Regional Original Revenue (PAD), which is a measuring tool in determining the ability of regions to finance the running of the wheels of government, must be strived to be improved in supporting services to the community. The strategy that can be done is to optimize the utilization of regionally owned assets. The financial capacity of the Ketapang Regency Government with PAD which is still below 10 percent reflects that the regional independence ratio is classified as